A novel immune checkpoint siglec-15 antibody inhibits LUAD by modulating mφ polarization in TME. (July 2022) - Xiao, Xuejun; Peng, Yan; Wang, Zheyue; Zhang, Louqian; Yang, Tingting; Sun, Yangyang; Chen, Yufeng; Zhang, Wenqing; Chang, Xinxia; Huang, Wen; Tian, Shuning; Feng, Zhenqing; et al.
Abstract: Background: Siglec-15 (S15) is a type-I transmembrane protein and is considered a new candidate of immune checkpoint inhibitor for cancer immunotherapy. Methods: In the present study, we first constructed and characterized a chimeric S15-specific monoclonal antibody (S15–4E6A). Then, the antitumor effectiveness and modulatory role of S15–4E6A in macrophages (mφs) were explored in vitro and in vivo. Finally, the underlying mechanism by which S15mAb inhibits LUAD was preliminarily explored. Results: The results demonstrated the successful construction of S15–4E6A, and S15–4E6A exerted an efficacious tumor-inhibitory effect on LUAD cells and xenografts. S15–4E6A could promote M1-mφ polarization while inhibiting M2-mφ polarization, both in vitro and in vivo. Conclusions: S15-based immunotherapy that functions by modulating mφ polarization may be a promising strategy for the treatment of S15-positive LUAD. Graphical Abstract: ga1